Study of Subsiding Trough Expansion Over Twin Tube TBM Metro Tunnel - Siemińska-Lewandowska A.; Kuszyk R. (Archives of Civil Engineering, 2018)
The main problem of tunnelling with use of TBM in highly dense urban areas is to assign the range of subsiding trough and the impact of tunnelling works on existing buildings and underground or road infrastructure. The paper presents the results of settlements calculations over twin tube metro tunnel using analytical, empirical methods. The tunnel external diameter is 6,5 m ; the overburden vary from 5 m to 8 m ; the distance between tunnel axis is 14 m. Because of quaternary soils and high water table level the TBM type EBP was chosen as the method of tunnel construction. At the length of 502 m of tunnel the monitoring system was carried out in 22 cross sections. The results of settlements monitoring were compared with the values of analytical calculations.